2015
DOI: 10.1161/jaha.115.002460
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mortality Following Acute Myocardial Infarction Among Dialysis Patients in the United States Over 15 Years

Abstract: BackgroundWe sought to determine 15‐year trends in mortality rates among dialysis patients with acute myocardial infarction (AMI) in the contemporary era.Methods and ResultsUsing the US Renal Data System database, we assembled 4 study cohorts of period‐prevalent dialysis patients in 1993, 1998, 2003, and 2008 who were hospitalized for an index AMI in that calendar year. ST‐segment elevation myocardial infarction (STEMI) and non‐STEMI were identified, and in‐hospital mortality was calculated. Cumulative probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 20 publications
(42 reference statements)
0
27
1
Order By: Relevance
“…44 Recent trends (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) show reduced in-hospital mortality from 32% to 18%, but this was apparent only among patients with ST segment elevation MI. 45 Chang et al 5 included a sizable representation of patients on dialysis with MI as index presentation (18% in the CABG arm and 26% in the PCI arm). In secondary analysis of prespecified subgroups, the authors reported that the overall study results of improved long-term survival with multivessel CABG versus PCI also applied to patients with MI on index presentation.…”
Section: Effect Of Acute Mi/acs On Revascularization Outcomesmentioning
confidence: 99%
“…44 Recent trends (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) show reduced in-hospital mortality from 32% to 18%, but this was apparent only among patients with ST segment elevation MI. 45 Chang et al 5 included a sizable representation of patients on dialysis with MI as index presentation (18% in the CABG arm and 26% in the PCI arm). In secondary analysis of prespecified subgroups, the authors reported that the overall study results of improved long-term survival with multivessel CABG versus PCI also applied to patients with MI on index presentation.…”
Section: Effect Of Acute Mi/acs On Revascularization Outcomesmentioning
confidence: 99%
“…3 As CKD progresses, the effect on outcomes worsens in a graded manner (Table 1). 5 Unfortunately, the risk posed to CKD patients does not end at the hospitalization. In patients with CKD, but not yet on dialysis (8.6% of patients), the adjusted mortality was almost double to 3.6%, the risk of bleeding increased to 6%, and the length of stay increased to 5.4 days.…”
Section: Introductionmentioning
confidence: 99%
“…and outcomes after PCI in dialysis patients remain unclear because the sample size of this group of patients is limited. [10][11][12][13][14][15] Although some previous studies have assessed clinical outcomes after PCI in dialysis patients with acute coronary syndrome (ACS), 5,11,16 few have specifically examined this matter in patients with stable CAD. 17 Such patients are often excluded from major clinical trials of cardiovascular interventions because of concerns regarding increased adverse events.…”
mentioning
confidence: 99%